1 thotsawat Saphā Thīprưksā Sētthakit læ Sangkhom hǣng Chāt (Samnakngān Saphā Thīprưksā Sētthakit læ Sangkhom hǣng Chāt, 2010)
On roles and activities of the National Economic and Social Advisory Council; volume brought out at occasion of 10th founding anniversary of the NESAC, Thailand.